Effects of Freezing and Thawing Cycle on Mechanical Properties and Stability of Soft Rock Slope - Yanlong Chen; Peng Wu; Qing Yu; Guang Xu (Advances in Materials Science and Engineering)
To explore the variation laws of mechanical parameters of soft rock and the formed slope stability, an experiment was carried out with collected soft rock material specimens and freezing and thawing cycle was designed. Meanwhile, a computational simulation analysis of the freezing-thawing slope stability was implemented. Key factors that influence the strength of frozen rock specimens were analyzed. Results showed that moisture content and the number of freezing-thawing cycles influenced mechanical parameters of soft rock significantly. With the increase of moisture content, cohesion of frozen soft rock specimens presents a quadratic function decrease and the internal friction angle shows a negative exponential decrease. The stability coefficient of soft rock material slope in seasonal freeze soil area declines continuously. With the increase of freezing and thawing cycle, both cohesion and internal friction angle of soft rock decrease exponentially. The higher the moisture content, the quicker the reduction. Such stability coefficient presents a negative exponential reduction. After three freezing and thawing cycles, the slope stability coefficient only changes slightly. Findings were finally verified by the filed database.